The Correlation Between Students’ Grammar Mastery on Simple Present Tenses and Speaking Ability in Describing People - Alda Najunda; Abdul Muin; Tri Ilma Septiana (ELITE JOURNAL, 2023)
ABSTRACT The main objective of this study was to examine the correlation between students’ grammar mastery and their speaking ability at the eighth grade of MTs Nurul Huda Baros. There is one research question in this study, which is “What is the relation-ship between students’ grammar mastery and speaking ability at the eighth grade of MTs Nurul Huda Baros?” This study used the correlation method and involved 31 students. In taking the sample of the research, the researcher used a cluster random sampling technique. To obtain valid and reliable data, the researcher conducted multiple choice for the grammar tests, and performance tests for the speaking test. The final finding of this study reveals that the significance test was 0.466. In other words, it can be interpreted that a significance level of 0.05 was 0.334. Due to the observed being higher than critical (0.466> 0.334). The conclusion of this study was that there was a correlation between students’ grammar mastery and their speaking ability in the eighth grade of MTs Nurul Huda Baros. Keywords: Correlation study; Grammar mastery; Speaking ability; Simple present tense